PERBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN USAHA KELOMPOK TANI BERBASIS TEKNOLOGI TEPAT GUNA DI DESA BUNUTAN KECAMATAN ABANG KABUPATEN KARANGASEM BALI - Penindra, I. M. D. B.; Purbant, I. G. R. (Buletin Udayana Mengabdi, 2016)
A total of 1534 households (2015) in the village of Bunutan constitute the majority of poor families who live in the mountains. There are so many poor households in the village of Bunutan, it becomes one of the targets of the program Study Field Experience Community Service (KKN PPM) Udayana University, where it will need community empowerment through mentoring by involving students under the coordination of the supervisor field. The programs that have been implemented include counseling and intensive training on organic fertilizer and biogas in Farmers Livestock Gunung Kembar, training fishing groups Mina Segara Langgeng about fish processing in the form of shredded meat and fish crackers, counseling to group Economic Empowerment Creative People on medicinal plant at the provision of seeds of medicinal plants and water pumps, the socialization of rabies and record wild dogs, training traditional dance for children, implementation of voluntary work in the office of the head of the village and its surroundings along with the office staff, the event execution voluntary work with the residents in the Gajah Wea Field, surgical stalls, garden arrangement in SD Negeri 8 Bunutan, manufacture boundary of the village, the arrangement of the library and provide books, provision of garbage bins, extension Correctural Posture, cleanliness of hands, feet and fingernails, oral hygiene in primary schools, the implementation of prevention exercise bone loss, blood sugar checks, examination of bone loss, and health talk shows, teaches basic lessons for children and youth, tropical tree planting around the neighborhood of the village of Bunutan.
Keywords: organic fertilizer; biogas; fish processing; correctural posture; rabies